Electronic Structure of Bis(4‐dimethylaminophenyl)squaraine. Issue 12 (26th March 2019) - Divya, Velayudhan V.; Suresh, Cherumuttathu H.
Abstract: The structural and electronic features of bis(4‐dimethylaminophenyl)squaraine (1 ) has been studied using density functional BLYP/ cc‐pVTZ level of theory. The quinoid character of 1 is correlated to the partial double bond character of C‐NMe2 (1.379 Å) and C−O (1.236 Å) bonds which leads to accumulation of positive charge on NMe2 groups and negative charge on carbonyl oxygen. Further, the diagonal C1 C3 (2.086 Å) and C2 C4 (2.116 Å) distances of the squaric ring indicated a 1, 3 type C−C orbital interaction. Molecular electrostatic potential (MESP) topographical analysis confirmed the charge separated quadrupolar nature of 1 . The MESP minimum, V min located at the carbonyl oxygen, −62.5 kcal/mol, confirmed its highly electron rich character arising from the quinoid structure. The electronic structure of 1 revealed from MESP confirmed its quadrupolar nature and suggested the location of positive charge on NMe2 groups. The typically used chemical structure drawing of 1 showing +2 charge on the squaraine ring is inaccurate and misleading. The solvatochromic behaviour of 1 can be attributed to its quadrupolar electronic structure wherein the electron rich carbonyl groups provide room for noncovalent interactions with multiple solvent molecules. Abstract : Molecular electrostatic potential analysis of the squaraine dye reveals its strong quadrupolar electronic structure, characterized by anionic oxygen centers and cationic NMe2 moieties. The sensitive solvatochromic behaviour of the dye is attributed to the ability of the oxygen centers to undergo significant non‐covalent interactions with multiple solvent molecules.